Student Perception of the Online Lecture System during the COVID-19 Period - Syafnan Syafnan; Mahyudin Ritonga; Fitriani Surayya Lubis (Yayasan Keluarga Guru Mandiri, 2022)
Lectures during the COVID-19 period at various universities worldwide and in Indonesia were specifically held online. However, this system faces serious problems, such as delays in students punctuality to the provided platform, and failure to complete assignments on time. Therefore, this study aims to analyze students' perceptions of the online lecture system during the COVID-19 period. It was conducted using a mixed-method approach, and the quantitative data were collected using surveys, while the qualitative were obtained using interviews, observations, and documentation. The results showed that the students responded negatively to the four aspects examined on the lecture system. This indicates that the online lecture system has not been fully implemented in Indonesia.